2017
DOI: 10.1136/emermed-2017-206692
|View full text |Cite
|
Sign up to set email alerts
|

Using an alumni survey to target improvements in an emergency medicine training programme

Abstract: Alumni self-evaluation of competence using the EM-Milestones provides valuable information concerning confidence to practice independently; these data, coupled with regular milestone evaluation of existing trainees, can identify problem areas and provide a blueprint for targeted programme improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our data demonstrate that SBP1 and SBP2 are the SCs for which fellows most commonly do not achieve at least a level 4 milestone score. These results are consistent with the 2018 ACGME report and studies that show low minimum scores for both SBP1 and SBP2 8,23 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data demonstrate that SBP1 and SBP2 are the SCs for which fellows most commonly do not achieve at least a level 4 milestone score. These results are consistent with the 2018 ACGME report and studies that show low minimum scores for both SBP1 and SBP2 8,23 …”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with the 2018 ACGME report and studies that show low minimum scores for both SBP1 and SBP2. 8,23 These SCs relate specifically to quality improvement and the implementation of systems improvements and require a trainee to make an impact outside of their institution in order to achieve at least a level 4. Quality improvement requirements in fellowship training are relatively new and mentors or leaders in this area may not be present at every program.…”
Section: Ta B L E 1 Demographic Information By Groupmentioning
confidence: 99%
“…6 Several articles to date have suggested that POCUS competencies are not being regularly met in many EM residency program settings. 1,3,[7][8][9] Most POCUS training workshops are one-half to two days in length and follow the traditional model of structured didactic sessions followed by hands-on training with human models or simulation units. 1,3,4 Some published studies on POCUS education and delivery models have shown positive learner outcomes; however, several have also indicated variable improvement across learners.…”
Section: Introductionmentioning
confidence: 99%